A Stylistic Analysis of Amos Tutuola’s Feather Woman of the Jungle - Betu, Donat Nkuna (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
In this article, we will deal with A Stylistic Analysis of Amos Tutuola’s Feather Woman of the Jungle, a novel written by Amos Tutuola. What we will aim to do is examine Tutuola’s manner of writing this novel, show the influence exerted by African oral literature upon this novel, and point out the most important figures of speech used by the author. In our article, we have been dealing with a stylistic analysis of the feathered woman of the jungle. This novel is written by Amos Tutuola, one of the distinguished Nigerian writers of the twentieth century, and as was already said, this novel contains a lot of literary techniques used by the author.